Correlation between Segmental Phoneme Pronunciation Accuracy and Verbal Performance - Divany, Adelia; Tambunan , Rahma; Lubis, Yani (CV. Generasi Insan Rafflesia, 2023)
Segmental phonetic articulation plays an important role in students' language performance.The purpose of this research is to show whether there is a correlation between accuracy. Pronunciation of segmental phonemes with the harmony of verbal language in english This study used a quantitative approach to the research design. Correlation. Samples are taken randomly or proportionally from each shift. 30 high school students participated in the partial random selection. collect skills Data on two variables with different speaking tests. Results of statistical analysis. The product moment correlation has value If rcount = 0.855 and rtable is 0.361 at a significance level of 0.05, then rcount > rtable. The coefficient of determination is 0.731 which means the yield is 73.1%. Linguistically determined by the correct pronunciation of the segment phonemes, the remaining 26.9 are determined by other factors. tcount(8.69) > ttable(1.701) proves its existence. Significant correlation. The results of this study indicate a relationship. Significant difference between segmental phoneme pronunciation accuracy and student performance word of mouth That's why teachers need to pay more attention. Partial phonemic understanding to avoid deep misunderstandings.